2009
DOI: 10.4244/eijv5i2a42
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dye injection on intracoronary pressure

Abstract: The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Contrast injection causes a temporal and small increase in intracoronary pressure during coronary angiography. Using a pressure guidewire, a previous study showed that the absolute and relative increase of mean intracoronary pressure due to manual contrast injection for angiography was 6.0 AE 4.2 mmHg and 6.7 AE4.9%, respectively [3]. Similarly, in the present study, the increase in intracoronary pressure due to automated contrast injection for angiography was small.…”
Section: Coronary Angiography and Intracoronary Pressure Increasesupporting
confidence: 64%
See 1 more Smart Citation
“…Contrast injection causes a temporal and small increase in intracoronary pressure during coronary angiography. Using a pressure guidewire, a previous study showed that the absolute and relative increase of mean intracoronary pressure due to manual contrast injection for angiography was 6.0 AE 4.2 mmHg and 6.7 AE4.9%, respectively [3]. Similarly, in the present study, the increase in intracoronary pressure due to automated contrast injection for angiography was small.…”
Section: Coronary Angiography and Intracoronary Pressure Increasesupporting
confidence: 64%
“…Since nearinfrared light is attenuated by red blood cells, OCT requires intracoronary injection of contrast media to remove blood from the field of view during the image acquisition. A previous coronary angiography study demonstrated that contrast injection caused a temporal increase in intracoronary pressure [3]. The excessive increase in intracoronary pressure may enlarge coronary artery dissections induced by catheters, guide wires, and/or angioplasty devices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…21 There was no statistical difference between intracoronary pressure increases measured at discrete distances from the catheter tip during coronary angiography in 6 patients. 22 While possibly not related to pressure increase, one basilar tip aneurysm rupture visualized during angiography occurred when the catheter-tip was at the junction of the subclavian and vertebral arteries, an estimated 37 cm away. 10 Retrograde brachial artery injections can cause pressure increases in the carotid 21 and a case report 8 showed contrast extravasation from potential re-rupture of an anterior communicating artery aneurysm during a brachial injection.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is clear that contrast injections cause a transient increase in intravascular pressure distal to the catheter-tip. [16][17][18][19][20][21][22][23][24] It is then reasonable to infer that increased intraneurysmal pressures during injections will cause ARAR in the setting of a ruptured and fragile aneurysmal wall 'sealed' with thrombus. 7,8,10,25,26 The fluid dynamics phenomena that occur at the catheter-tip during contrast injections are extremely complex involving the dispersion and mixing of a potentially turbulent contrast jet with co-flowing laminar pulsatile blood flow and associated vortical flow structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation